Developing a hierarchical analytical process to determine the best irrigation system for date palm trees in the NENA region: the case of Iran - Naeini, Mahkameh S.; Nazari, Bijan; Liaghat, Abdolmajid (Applied water science, 2025)
The NENA region faces serious challenges in achieving sustainable development due to water scarcity problems, especially in the agricultural sector. Identifying the most effective irrigation method for agricultural fields can have a positive impact on water consumption and management in this region. The purpose of this study is to develop an analytical hierarchy process for determining the best irrigation system for date palm trees in the NENA region. Iran was selected as the case study, and the Expert Choice software was used. Using document studies, library and field data, and the opinions of 42 experts, the most important criteria and sub-criteria were identified. Based on the results of the evaluations, there were 39.1%, 8.9%, 21.0%, 19.9%, and 11.0% effects of technical, economic, social, operation and maintenance, and environmental criteria on selecting the suitable irrigation system, respectively. For palm fields in Khuzestan, a furrow irrigation system with low-pressure water distribution pipes was determined to be the most appropriate irrigation system. The bubbler irrigation system is the most suitable irrigation system for Bushehr. In Kerman, Sistan, and Baluchestan, bubbler and sprayer irrigation systems were introduced as the most effective irrigation systems. Using the model presented in this study, useful, comprehensive, and practical results can be obtained for evaluating and ranking irrigation systems in the NENA region and similar water-scarce arid regions. It is also suggested that a database for palm irrigation be developed in the NENA region in order to achieve the goals of sustainable development.